Length-dependent photo-electrochemical performance of vertically aligned hematite nanorods. (September 2020) - Kong, Heejung; Jung, Jinjoo; Hwang, Suwon; Park, Jaemin; Kim, Do Hyung; Yeo, Junyeob
Abstract: Photo-electrochemical (PEC) cells have been widely studied as an eco-friendly method of producing hydrogen fuel. Among the various materials, hematite (α-Fe2 O3 ) is one of the most promising candidates for PEC applications due to its chemical stability and visible-range bandgap. However, despite the aforementioned advantages, hematite-based PEC cells have suffered from an extremely short hole diffusion length and charge carrier lifetime, resulting in a solar-to-hydrogen efficiency far lower than the theoretical maximum. To overcome these drawbacks, we controlled the length of vertically aligned hematite nanorod (NRs) arrays on a fluorine-doped tin oxide substrate by adjusting the chemical concentrations of the precursor solutions. We confirmed that the PEC performance of the hematite NRs was strongly dependent on their length and showed an approximately inverse proportionality between the length of the hematite NRs and their photoactivity. In addition, the hematite NRs array, with an optimized length, was further modified by cobalt phosphate (Co-Pi) cocatalysts to enhance the water oxidation kinetics and showed 1.54 mA cm −2 of photocurrent at 1.23 V vs. RHE. Highlights: We controlled the length of vertically aligned hematite NRs by adjusting the chemical concentrations. The PEC performance of vertically aligned hematite NRs was strongly dependent on the length of the NRs. For the 800 °C high-temperature annealing, the optimal length of NRs yielding the best PEC performance was 300–500 nm. The cobalt phosphate modified hematite NRs showed 1.54 mA·cm-2 of photocurrent at 1.23 V vs. RHE.